Developing Children's Cognitive Ability In Numerating Objects At At-Tibyan Kindergarten, Banjarmasin, Indonesia - Noor Halida Yanti; Nurilla Santi; Rizki Nugerahani Elise (Tajdid Al-Athfal, 2021)
Study used a classroom action research design and was carried out in 4 meetings. The subjects of this study were group B children at Al-Badariyah Kindergarten, Banjarmasin City, totaling 13 children. The type of research data used is qualitative data. The assessment instrument used is an observation sheet for teacher and child activities taken during the learning process. Descriptive qualitative data analysis in the form of tables, graphs and interpretations using presentations. The indicators of the success of this research are the teacher's activities get a score of 30 in the "very good" category, the average class activity of children with a percentage of 80% is included in the active and very active category, and the child's development results get a minimum of stars (BSH) . The results showed that the combination of the explicit instruction model and the numbered head together model and the congklak game and singing method could increase teacher activity from getting a score of 25 to a score of 35 at meeting 4 with the criteria of "very good". Children's activities from getting a value of 15% developed to 92% at meeting 4, on the results of the achievement of children's cognitive development in counting objects, it was said to have succeeded with 13 children who got (BSH) and (BSB) with 100% percentage.